Bahasa Isyarat Sebagai Alat Komunikasi Dalam Konteks Adat dan Hukum Suku Korowai - Susilawati, Efi; Kurnia, Heni; Kurnia, Heri; Pebriyanti, Indah (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
This article discusses the use of sign language in the customary communication and law of the Korowai tribe in Papua, Indonesia. The Korowai tribe possesses a unique culture that has existed for hundreds of years. This research shows that sign language reflects their cultural and legal values, being used in various social situations, from family gatherings to legal decision-making processes. Sign language is considered more polite in certain contexts and helps strengthen relationships among tribe members. The journal also examines how sign language plays a role in preserving traditions and understanding customary values, ensuring the safety and harmony of the community. These findings are expected to enrich anthropological and linguistic studies, as well as enhance understanding of the cultural diversity of indigenous peoples in Indonesia and around the world.